DUKUNGAN SUAMI TERHADAP KEBERHASILAN PEMBERIAN ASI EKSLUSIF PADA IBU BEKERJA - Elly Dwi Wahyuni (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2020)
ABSTRACT Background: The level of participation of women workers increased from 48.63% to 49.52%. Data from the Central Statistics Agency show that there are currently 81.5 million female workers. Many factors are believed to influence the success of exclusive breastfeeding.Many factors are believed to be the success of this exclusive breast-milk. Support to the mother is an important factor that also affects the mother to give exclusive breast milk. One of the most influential support is husband's support.Purpose: To know the relationship between husband's support to the success of exclusive BREAST feeding on mothers working at the main hospitalisationMethod: Descriptive analytics with cross sectional. Sampling using a random sampling survey formula. The data used is the primary data by giving a poll to the respondent. Univariate analysis, bivariate and multivariate. Results: The analysis of the relationship between the husband's support to success in the giving of exclusive breast milk to work is obtained in the form of Emosioanl support P = 0.000, physical support p = 0.000, support information p = 0.000 and support assessment P = 0,000, to The result of a multivariate of physical support OR 18.2 has the opportunity to have the success of the exclusive ASI 18.2 times greater than the group who did not get Fsik support less well after controlled with the other support.Conclusion: There is a relationship between the support of husband to success in the giving of exclusive breast milk work at the main hospitalization in Depok JayaSugestion: For further research, it is necessary to conduct further research on the factors that can influence the attitudes of mothers and understanding of working mothers and motivation in exclusive breastfeeding and research using qualitative studies on mothers' experiences in exclusive breastfeeding. Keywords: husband support, exclusive ASI success, worker mothers ABSTRAK Latar Belakang : Tingkat partisipasi pekerja perempuan meningkat dari 48,63% menjadi 49,52%. Data Badan Pusat Statistik menunjukan pekerja perempuan jumlahnya sekarang 81,5 juta orang. Masih banyak ibu menyusui yang bekerja sehingga tidak bisa memberikan ASI eksklusif kepada bayinya atau kurang optimal dalam memberikan ASI eksklusif Banyak faktor yang dipercaya dapat mempengaruhi keberhasilan pemberian ASI ekslusif ini. Salah satu dukungan yang paling berpengaruh adalah dukungan suami.Tujuan: Mengetahui hubungan antara dukungan suami terhadap keberhasilan Pemberian ASI Ekslusif pada ibu bekerja di Klinik Utama Rawat Inap Depok JayaMetode :Deskriptif Analitik secara cross sectional. Pengambilan sampel dengan menggunakan rumus samplessurvey random sampling. Data yang digunakan adalah data primer dengan memberikan angket kepada responden. Analisis Univariat, Bivariat dan Multivariat.Hasil: Hasil analisis hubungan antara dukungan suami terhadap keberhasilan dalam pemberian ASI Ekslusif pada Ibu bekerja didapatkan berupa Dukungan Emosioanl p= 0,000, dukungan fisik p= 0,000, dukungan informasi p= 0,000 dan dukungan penilaian p=0,000, Untuk hasil multivariate dukungan fisik OR 18,2 ini berpeluang memiliki keberhasilan ASI eksklusif 18,2 kali lebih besar dibanding kelompok yang tidak mendapatkan dukungan fsik kurang baik setelah dikontrol dengan dukungan yang lainnya.Kesimpulan: Terdapat hubungan antara dukungan suami terhadap keberhasilan dalam pemberian ASI Ekslusif pada Ibu bekerja di Klinik Utama Rawat Inap Depok JayaSaran: Untuk penelitian selanjutnya perlu mengadakan penelitian lebih lanjut mengenai faktor – faktor yang dapat mempengaruhi sikap ibu dan pemahaman ibu bekerja dan motivasi dalam pemberian ASI eksklusif dan penelitian menggunakan studi kualitatif tentang pengalaman ibu dalam pemberian ASI eksklusif Kata Kunci : Dukungan Suami, Keberhasilan ASI Ekslusif, Ibu Pekerja,